Improving the Accessibility of Investigation Reports Using Safety Factor Maps. (January 2013) - Wiggins, Mark W.; Glass, Renee
Safety factor maps can provide a visual summary of the events associated with accidents and incidents. Because they employ conceptual mapping techniques, they enable both a hierarchical and temporal representation of the antecedents of an adverse event. We describe the development of safety factor maps and a strategy to assess both the reliability and the validity of the maps that are constructed. Our initial findings suggest that they have the potential to improve the accessibility of the outcomes of investigation reports.